A Single “All-in-One” Helper-Dependent Adenovirus to Deliver Donor DNA and CRISPR/Cas9 for Efficient Homology-Directed Repair - Palmer, Donna J. (Mol Ther Methods Clin Dev, 2020)
In this study, we developed a single helper-dependent adenovirus (HDAd) to deliver all of the components (donor DNA, CRISPR-associated protein 9 [Cas9], and guide RNA [gRNA]) needed to achieve high-efficiency gene targeting and homology-directed repair in transduced cells. We show that these “all-in-one” HDAds are up to 117-fold more efficient at gene targeting than donor HDAds that do not express CRISPR/Cas9 in human induced pluripotent stem cells (iPSCs). The vast majority (>90%) of targeted recombinants had only one allele targeted, and this was accompanied by high-frequency indel formation in the non-targeted allele at the site of Cas9 cleavage. These indels varied in size and nature, and included large deletions of ∼8 kb. The remaining minority of recombinants had both alleles targeted (so-called bi-allelic targeting). These all-in-one HDAds represent an important platform for accomplishing and expanding the utility of homology-directed repair, especially for difficult-to-transfect cells and for in vivo applications.